Two Consecutive Runs of Veno-Venous Extracorporeal Membrane Oxygenation in a Peripartum Patient with COVID-19 Acute Respiratory Distress Syndrome - Nicolò Sella; Tommaso Pettenuzzo; Michele Della Paolera; Giulio Andreatta; Annalisa Boscolo; Alessandro De Cassai; Luisa Muraro; Arianna Peralta; Paolo Persona; Enrico Petranzan; Francesco Zarantonello; Eugenio Serra; et al. (Case Reports in Critical Care)
Veno-venous extracorporeal membrane oxygenation (V-V ECMO) may be required to treat critically ill patients with COVID-19-associated severe acute respiratory distress syndrome (ARDS). We report the case of a 43-year-old peripartum patient, who underwent two sequential V-V ECMO runs. The first extracorporeal support was established for COVID-19 ARDS, as characterized by severe hypoxemia and hypercapnia (arterial partial pressure of oxygen to inspired oxygen fraction ratio 85 mmHg and arterial partial pressure of carbon dioxide 95 mmHg) and reduction of respiratory system static compliance to 25 mL/cmH2O, unresponsive to mechanical ventilation and prone positioning. After 22 days of lung rest, V-V ECMO was successfully removed and ventilator weaning initiated. A second V-V ECMO was required 7 days later, because of newly onset ARDS due to Pseudomonas aeruginosa ventilator-associated pneumonia. The second V-V ECMO run lasted 12 days. During both V-V ECMO runs, anticoagulation and ventilator settings were titrated through bedside thromboelastometry and electrical impedance tomography, respectively, without major complications. The patient was successfully decannulated, weaned from mechanical ventilation, and finally discharged home without oxygen therapy. At one-month follow-up, she showed good general conditions and no sign of respiratory failure.